2000
DOI: 10.1053/joca.1999.0266
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis in bovine articular chondrocyte by prostaglandin E2through cAMP-dependent pathway

Abstract: It is the first report that PGE(2) can induce articular chondrocyte apoptosis in vitro. It is also suggest that apoptosis of chondrocytes by PGE(2) is linked with cAMP-dependent pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
1
6

Year Published

2000
2000
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 42 publications
2
64
1
6
Order By: Relevance
“…Increased apoptosis has been observed in chondrocytes treated with exogenous PGE 2 and is coupled with increased cAMP (46,47); however, effects on mitochondria have not been reported. Conversely, PGE 2 has been shown to mediate apoptotic resistance in other cell types, including cancer cells (48,49) and gastric mucosal cells (50) via mitochondrion-dependent pathways.…”
Section: Discussionmentioning
confidence: 97%
“…Increased apoptosis has been observed in chondrocytes treated with exogenous PGE 2 and is coupled with increased cAMP (46,47); however, effects on mitochondria have not been reported. Conversely, PGE 2 has been shown to mediate apoptotic resistance in other cell types, including cancer cells (48,49) and gastric mucosal cells (50) via mitochondrion-dependent pathways.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, low concentrations of PGE 2 may downregulate collagenases and collagen 2A1 cleavage [38]. PGE 2 may enhance chondrocyte death [39] and induce apoptosis in bovine articular chondrocytes through the cAMP pathway [40]. In this study, we investigated the effects of HO-1 induction on IL-1-stimulated PGE 2 production in primary OA chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using bovine normal articular chondrocyte has demonstrated that even PGE 2 itself induced DNA fragmentation of the cells, as determined by ELISA (55). This controversy may be due to differences in culture conditions and/or cartilage specimen used for cell culture.…”
Section: Discussionmentioning
confidence: 99%